From the idea of justice to the idea of injustice: Mixing the ideal, non-ideal and dynamic conceptions of injustice - Oscar Garza (University of Bath, Centre for Development Studies (CDS), 2013)
Recent legal reforms in Mexico demonstrate that, it, like many other countries, still relies on an understanding of development as economic growth in order to justify social policies. The widespread social costs of this framework, however, demand now more than ever before a framework of social justice that can counteract the justification and legitimisation of social policies solely based on such a view of development. While there is a strong demand for social justice to inform political action, in recent years, ideal theories of justice have also come under severe criticism due to their (apparent) lack of practical policy relevance. This paper departs from this view and argues that ideal theories are essential for the reduction of injustice in the present but that it is necessary to reconcile and complement ideal and non-ideal approaches to justice. The paper takes Rawls's Theory of Justice and Sen's Idea of Justice as illustrations of my argument. In the light of the labour reform in Mexico, this paper, however, argues that both ideal and non-ideal conceptions of justice are necessary but are still insufficient in reducing injustice. Without a dynamic understanding of injustice and how it is reproduced, approaches to social justice would remain transcendental and, thus, their effective applicability in the real world is highly compromised. This implies the need to go beyond the usual all-purpose conceptions of justice (whether ideal or non-ideal) and establish what the paper calls a 'multi-level' conception of justice to effectively inform social policies and reduce injustice 'in the real world'.
Keywords: 330; Social justice and injustice; labour reform; development; social policy; ideal and nonideal theories of justice; Mexico